(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the famous Ukrainian archaeologist S.Maghura who lived and worked in the first half of the XX century. The author paid attention to the impact of M.Makarenko on the creation of S. Maghura as one of the leading specialists in the field of archaeological investigations.